PENERAPAN KONSEP TRI N “NITENI, NIROKAKE, NAMBAHI’’ DALAM STRATEGY PEMASARAN DIGITAL PADA UMKM CV SAVITA INDONESIA - Paryanto, Alfin Dwi; Garnita, Ria; Lindawati, Lindawati; Septiani, Rizka Ayu; Aldo, Ketut; Reo, Petrus Renol; Purnamarini, Tri Ratna (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
This community service aims to provide in-depth understanding and share experiences regarding the application of Tamansiswa teachings, especially the Tri N concept: "Niteni, Nirokake, Nambahi," in marketing strategies in the digital era for CV Savita Indonesia. This activity was carried out for three days in Kulon, Sinduharjo, Kec. Ngaglik, Sleman Regency. The methods used in this community service are direct observation and interviews with business actors, so that the information obtained is more accurate and relevant. The Tri N concept is applied as a basis for designing an effective digital marketing strategy, including observation (Niteni), analysis (Nirokake), and development (Nambahi). The results of this activity show an increase in understanding and implementation of Tri N teachings in CV Savita Indonesia's digital marketing strategy, which is expected to increase competitiveness and business sustainability in the digital market